2016
DOI: 10.1038/ncomms12738
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants for the strictly compartmentalized expression of kainate receptors in CA3 pyramidal cells

Abstract: Distinct subtypes of ionotropic glutamate receptors can segregate to specific synaptic inputs in a given neuron. Using functional mapping by focal glutamate uncaging in CA3 pyramidal cells (PCs), we observe that kainate receptors (KARs) are strictly confined to the postsynaptic elements of mossy fibre (mf) synapses and excluded from other glutamatergic inputs and from extrasynaptic compartments. By molecular replacement in organotypic slices from GluK2 knockout mice, we show that the faithful rescue of KAR seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Thus, they may take on new functions as the animal develops. Consistent with this, cadherins function in diverse processes including neural tube formation (Hirano and Takeichi, 2012), axon targeting (Duan et al, 2014; Kuwako et al, 2014; Osterhout et al, 2011; Poskanzer et al, 2003), synapse formation (Togashi et al, 2002; Williams et al, 2011), synapse pruning (Bian et al, 2015), and synapse function (Bozdagi et al, 2010; Fièvre et al, 2016; Jungling et al, 2006; Mendez et al, 2010; Tang et al, 1998; Vitureira et al, 2011). Moreover, there is an overwhelming focus on the study and function of the broadly expressed N-cadherin/cadherin-2 and β-catenin, an intracellular binding partner common to all classic cadherins.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, they may take on new functions as the animal develops. Consistent with this, cadherins function in diverse processes including neural tube formation (Hirano and Takeichi, 2012), axon targeting (Duan et al, 2014; Kuwako et al, 2014; Osterhout et al, 2011; Poskanzer et al, 2003), synapse formation (Togashi et al, 2002; Williams et al, 2011), synapse pruning (Bian et al, 2015), and synapse function (Bozdagi et al, 2010; Fièvre et al, 2016; Jungling et al, 2006; Mendez et al, 2010; Tang et al, 1998; Vitureira et al, 2011). Moreover, there is an overwhelming focus on the study and function of the broadly expressed N-cadherin/cadherin-2 and β-catenin, an intracellular binding partner common to all classic cadherins.…”
Section: Discussionmentioning
confidence: 62%
“…Several studies indicate that differential matching of Type II cadherins provides an adhesive code driving specific synapse formation (Duan et al, 2014; Kuwako et al, 2014; Osterhout et al, 2011; Poskanzer et al, 2003; Redies and Takeichi, 1996; Suzuki et al, 1997; Williams et al, 2011). Moreover, cadherins localize at synapses and regulate many synaptic functions including synaptic vesicle clustering, dendritic spine stabilization, glutamate receptor recruitment, short-term plasticity, and long-term plasticity (Aiga et al, 2010; Bozdagi et al, 2010; Fièvre et al, 2016; Hirano and Takeichi, 2012; Jungling et al, 2006; Mendez et al, 2010; Saglietti et al, 2007a; Tang et al, 1998; Togashi et al, 2002; Vitureira et al, 2011). However, the majority of these functional studies only investigated the role of cadherin-2 (also known as N-cadherin).…”
Section: Introductionmentioning
confidence: 99%
“…Previous results have shown that GluK2 expression is important for physiological surface expression of KCC2 and corresponding chloride transport in cortical neurons (Mahadevan et al, 2014 ; Pressey et al, 2017 ; Garand et al, 2019 ). To validate the role of GluK2 in regulating KCC2 in vivo , we used lentiviral shRNA (shRNA GluK2 -EGFP) for local silencing of GluK2 in WT mice CA3 pyramidal neurons, where endogenous GluK2 is strongly expressed in dendrites (Fièvre et al, 2016 ). Control animals were injected with lentivirus encoding for EGFP.…”
Section: Resultsmentioning
confidence: 99%
“…In postnatal, excitatory synapses, N-cadherin is required for LTP and spine enlargement—but not LTD or spine density and morphology, suggesting that cadherins selectively regulate synapse plasticity (Bozdagi et al, 2010). Indeed, cadherin accumulation on synaptic membranes is required for stabilizing postsynaptic receptors, e.g., kainate receptors (Fièvre et al, 2016) and AMPAR (Mills et al, 2017). Catenins also regulate synapses: upon NMDAR activation, β-catenin is redistributed from the dendrite shaft to the spines (where it binds N-cadherin), leading to synapse enlargement, consistent with its role in learning and memory (Murase et al, 2002).…”
Section: Cell Adhesion Molecules Initiate Specify and Regulate Synapsesmentioning
confidence: 99%